Risk Management In Private Legal Practice In Malaysia= Time For A Rethink - Norman Zakiyy Chow Jen-T'Chiang (Universiti Sains Islam Malaysia, 2024)
In Malaysia, most law schools throughout the country, has either not given or given little emphasis on the need to expose law students to the study, of risk management. Senior practitioners, young practitioners and even pupils in chamber would have a competitive advantage if they are aware of the risk of common claims and the necessary steps which can be taken to alleviate or avoid a particular risk common to the practice of law. In the light of the above considerations, the writer intends to discuss risk in the practice of law in Malaysia and how risk should be shaped and contained and not shunned or avoided at all costs. To achieve this, the writer introduces the types of risk in legal practice and further discusses the possible and current practical methods which can be adopted to alleviate or minimize risk in legal practice.